THE UTILITY OF BIOPSYING ENDOSCOPICALLY NORMAL APPEARING TERMINAL ILEUM. (26th January 2023) - Vora, Haily; Ibrahim, Ramez; Johanna, Chan; Farraye, Francis; Al Hashash, Jana
Abstract: INTRODUCTION: The terminal ileum is often evaluated during colonoscopy procedures. A common indication for endoscopic examination and biopsy of an endoscopically normal appearing terminal ileum is in patients with inflammatory bowel disease (IBD). 1 In patients without IBD, indications for biopsying an endoscopically normal appearing terminal ileum are less clear and may be associated with increased cost and healthcare utilization, as well as increased levels of anxiety for patients. In this study, we aim to determine the indications for examining and biopsying an endoscopically normal appearing terminal ileum in patients without IBD and if, upon review of these biopsies, there is change in management. METHODS: This was a retrospective chart review of patients who underwent colonoscopy with terminal ileum biopsy at Mayo Clinic between 1/1/2021 and 6/30/21. Patients were excluded if they had a history of IBD, prior ileocecal resection, or an endoscopically abnormal terminal ileum. Clinical and laboratory data, as well as outcomes of interest, were obtained from the electronic medical record. Comparisons between patients were performed using Pearson's chi-square, Student's and Mann-Whitney tests. RESULTS: A total of two hundred consecutive patients were identified as having had biopsies from their endoscopically normal appearing terminal ileum. After reviewing the charts, 69 met inclusion criteria. Of the 69 patients, the majority were female (68.1%) and white (89.9%). Nearly half the patients had a BMI of 30 or above (49.3%). The most common indication for colonoscopy among these patients was chronic diarrhea followed by abdominal pain and hematochezia. Terminal ileum mucosa was histologically abnormal in 6 patients (8.7%): four patients had chronic ileitis, one had acute ileitis, and one had acute and chronic ileitis. All patients with either chronic or acute ileitis had chronic diarrhea listed as an indication for their colonoscopy. The patient with acute and chronic ileitis underwent colonoscopy for suspected Crohn's disease due to incidental asymptomatic findings of small bowel inflammation on CT enterography. CONCLUSIONS: In patients with a normal appearing terminal ileum, clinically significant histologic abnormalities on biopsies were found in a small percentage of patients. Although our sample size is small, there may not be diagnostic and therapeutic utility to routinely biopsy endoscopically normal appearing terminal ileum in patients, even in those with chronic diarrhea. Large prospective studies are needed to further support this observation. REFERENCES: 1 McHugh, Jonathan B et al. "The diagnostic value of endoscopic terminal ileum biopsies." The American journal of gastroenterology vol. 102, 5 (2007): 1084-9.